Analysis of WEDM process parameters on surface roughness and kerf using Taguchi method - Banu, Asfana; Bakar, Mazilah Abu; Ali, Mohammad Yeakub; Adesta, Erry Yulian Triblas (Deer Hill Publications, 2017)
In obtaining the best quality of engineering parts, the quality of machined surface plays an essential role. The fatigue strength, wear resistance, and corrosion of workpiece are some of the aspects of the qualities that can be improved. This paper investigates the effect of wire electrical discharge machining (WEDM) process parameters on surface roughness and kerf on stainless steel using distilled water as dielectric fluid and brass wire as tool electrode. The selected process parameters are voltage open, wire speed, wire tension, voltage gap, and off time. Empirical models using Taguchi method were developed for the estimation of surface roughness and kerf. The analysis revealed that off time has major influence on surface roughness and kerf. The optimum machining parameters for minimum surface roughness and kerf were found to be 10 V open voltage, 2.84 μs off time, 12 m/min wire speed, 6.3 N wire tension, and 54.91 V voltage gap.